Developing Early Childhood’s Fine Motor Skills through Various Learning Activities: A Study Case at Ummul Habibah Pre-School, Klambir V Kebun Village - Rita Nofianti; Abdi Syahrial Harahap; Nursaida Yanti (COMPASS: Journal of Education and Counselling, 2024)
Fine motor is a movement that only involves certain parts of the body and is carried out by small muscles such as skills using fingers and precise wrist movements. Motor development in early childhood can be done by developing children's creativity. Childhood has the potential to master various skills in conquering the surrounding environment so that in developing their skills, children always do various fun activities that are carried out repeatedly, therefore, children are very happy in doing activities in developing motor skills. This research was done in describing kinds and benefits of activities which can be done to develop earl childhood’s fine motor skills. Through library research, this study employed a descriptive qualitative methodology and the literature study method. It was found that the better the child's fine motor movements, the more creative the child can be, such as cutting paper and weaving paper, but not all children have the maturity to master the skills at the same stage. In performing fine motor movements, children also need the support of physical skills and mental challenges. Early childhood fine motor skills can be improved through various activities using various media that have been provided by the teacher concerned. Through collage activities with various materials, folding origami paper, and also painting with fingers has been proven to be able to improve fine motor skills in early childhood.